A Laboratory Evaluation for the Potential of Entomopathogenic Fungi against Tribolium castaneum (Herbst.) (Coleoptera: Tenebrionidae) - Muhammad Akmal; Shoaib Freed; Muhammad Bilal; Muhammad Naeem Malik (Turkish Journal of Agriculture: Food Science and Technology)
The red flour beetle is a very important primary insect pest of wheat worldwide. The experiments were performed to check the virulence of Beauveria bassiana and Isaria fumosorosea by insect dipping method on the adults and 2nd instar of Tribolium castaneum. Conidia were taken from 15 days old fungi and subsequently four concentrations i.e., 2×108, 3×108, 4×108 and 5×108 spores/ml of both fungi were prepared in 0.05% Tween 80 solution. Minimum 12.5% and maximum 32.5% mortality of adult insects was recorded on 7th day after the treatment at 2×108 and 5×108 spores/ml concentrations of B. bassiana, respectively while on larval stages, minimum 2.5% on 5th day and maximum 80.0% mortality was observed on 7th day post treatment of B. bassiana, respectively. On the other side, minimum 7.5 and maximum 22.5 mortality percentage was noted on 7th day post application of I. fumosorosea, respectively while on immatures minimum 5% on 6th day and highest 70% mortality was noted on 7th day post infection with 2×108 and 5×108 spores/ml of I. fumosorosea, correspondingly. This study showed the effectiveness of insect pathogenic fungi against the important stored grain insect pest and proved to be a positive management strategy.